Cooling machine on the highboiling substances - Чеканова, Наталья Николаевна (Technology audit and production reserves, 2014)
The general idea of the proposed machines consists of employing a low-pressure aggregate (p<1 bar) – vacuum pump instead of traditionally used compressor. Owing to the fact that mechanical loads of low-pressure systems proposed are comparatively not very high, such systems possess a number of advantages comparing to the high-pressure ones: safety, longevity, reliability, a less metal capacity, etc. The proposed as a heat pump and refrigerator make possible using of the wide range of high boiling and ecologically clean substances as cooling agent, for example, ethanol, methanol and its water solution, etc. The cooling substance is selected in dependence of the required temperature, considering the safety of exploitation and ecological safety of the substance and its production. These machines do not destroy the ozone layer of the Earth and the heat pump does not cause a heat contamination for the atmosphere and saves the high-quality fuel substances such as gas, oil and coal.